Studi Literatur: Peranan Pekerja Sosial Dalam Pencegahan Kekerasan Dalam Rumah Tangga - Susanti, Sani; Siregar, David; Maharani, Nabila; Simaremare, Paskah Aritonang; Zai, Ribka Eirene (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This literature study aims to analyze the role of social workers in preventing domestic violence. Through analysis of various scientific sources, it was found that social workers have a crucial role in efforts to prevent domestic violence. The social worker's role involves cross-sectoral collaboration with various agencies to provide a comprehensive response to domestic violence. Training programs are needed that focus on increasing the competency of social workers in handling cases of violence effectively. Support for victims, including access to health and psychosocial services, as well as rehabilitation and reintegration into society, is also an important aspect of the social worker's role. These findings emphasize the important role of social workers in creating an environment that is safe and free from domestic violence through various comprehensive and sustainable prevention strategies.